EDUKASI MODERASI BERAGAMA MELALUI SUB-CPMK AGAMA KATOLIK KEBAJIKAN BIBLIS DENGAN METODE PjBL DI PERGURUAN TINGGI - Hayon, Vinsensius (STIPAS Keuskupan Agung Kupang, 2024)
The acceleration of progress in the field of Science and Technology (Science and Technology) can be felt and has unlimited effects in various areas of life. All progress movements are covered in and within the realm of globalization mobility and the domain of Industrial Revolution 4.0. The effect is very pronounced and its influence penetrates very quickly into the realm of education, thus influencing the attitude of life of students as a young generation. In connection with relations and interactions between students and between religious communities, great efforts are made to construct an understanding of moderate religious practices so as not to fall into radical and exclusive, extreme and intolerant positions. Therefore,